2017
DOI: 10.1039/c7ra07321f
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring silica–rubber interactions by interface modifiers with multiple functional groups

Abstract: Tailoring silica–rubber interactions using TMPMP (TV0) and single (TV1), double (TV2) and triple (TV3) VTES modified TMPMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…4(a). The high G 0 level at lower strains and its rapid decline at higher strains is called Payne effect, [26][27][28] which is mainly caused by the existence of ller network under lower strains and its progressive collapse and destruction under higher strains. [29][30][31] As can be seen, with more addition of VMQ, G 0 of NR/VMQ increases, which indicates stronger structure of ller network.…”
Section: Filler Network and Dispersion Morphologymentioning
confidence: 99%
“…4(a). The high G 0 level at lower strains and its rapid decline at higher strains is called Payne effect, [26][27][28] which is mainly caused by the existence of ller network under lower strains and its progressive collapse and destruction under higher strains. [29][30][31] As can be seen, with more addition of VMQ, G 0 of NR/VMQ increases, which indicates stronger structure of ller network.…”
Section: Filler Network and Dispersion Morphologymentioning
confidence: 99%
“…However, the dispersibility of silica in the composite material is rather poor and the agglomeration is serious because of the large quantities of silanol groups on the surface of silica and high surface energy [ 16 , 17 , 18 , 19 ]. Therefore, improving the dispersion [ 20 , 21 , 22 , 23 , 24 ] of silica in composite materials by pretreatment is a hot research topic [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, owing to the large difference in saturating degree and surface characteristics, it is quite difficult to compound saturated VMQ of a low surface energy with unsaturated rubber of a high surface energy, 7,9 such as the styrene−butadiene rubber (SBR), butadiene rubber (BR), and NR. In our previous studies, SBR/VMQ composites have been prepared, which focused on strengthening the interfacial compatibility 10 and rubber−filler interaction 11,12 in addition, the relationship between aging properties and phase morphology of BR/VMQ composites has also been studied. 13 There have been few studies reported on NR/VMQ composites earlier; for instance, Kim et al 14 have studied the effect of bifunctional silane bis(triethoxysilylpropyl)disulfide (TESPD) on the vibrational, thermal, and mechanical properties of VMQ/NR/silica composites; the influences of a grafted-polysiloxane compatibilizer on the miscibility of NR/ VMQ composites have been studied by Zhang et al 15 For obtaining homogeneous composites with collaborative performances, enhancement of interfacial compatibility between NR and VMQ is essential.…”
Section: Introductionmentioning
confidence: 99%